Students’ Perception Towards Orai As Learning Media Of Speaking Skill At Grade Eight Of SMP Negeri 1 Pematang Siantar - Meliana Br.Siahaan; Tiarma Intan Marpaung; David Togi Hutahaean (CV Putra Publisher, 2024)
Orai application is an online public speaking course application designed to overcome the problem of speaking with intonation and pacing from the basis of practice. This research aims to determine students' perceptions towards Orai as learning media of speaking skills in grade VIII of SMP N 1 Pematang Siantar. In this research, the data collection instruments used were observation sheet and questionnaires sheet. Observation was used to observe English teaching and le arning activities in using the Orai application. The questionnaire sheet consists of twenty statements regarding student perceptions of the use Orai application made in a Google Form. The source of data in this research was taken from students of grade VIII-2. There were 20 participants selected as samples in this research. This research used a qualitative method with a descriptive design. Findings from the results of data analysis, students have positive and negative perceptions of the use Orai application as an English learning media. There were 19 statements included in the positive perception with a percentage of 95% and there was 1 statement with a percentage of 5%. Hadi (2018)) stated that perception has 2 types, namely positive and negative. Most participants have a positive perception of Orai as learning media speaking skill with the majority of answers chosen by students strongly agree that Orai is very helpful in learning English.